2021
DOI: 10.1177/24725552211023214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Very Deep Convolutional Neural Networks for Nucleus Segmentation from Brightfield Cell Microscopy Images

Abstract: Advances in microscopy have increased output data volumes, and powerful image analysis methods are required to match. In particular, finding and characterizing nuclei from microscopy images, a core cytometry task, remains difficult to automate. While deep learning models have given encouraging results on this problem, the most powerful approaches have not yet been tested for attacking it. Here, we review and evaluate state-of-the-art very deep convolutional neural network architectures and training strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The focal plane had been manually chosen in a prior step. As it has been previously shown that similar DL network architectures require considerably more bright-field data to converge to an optimal solution compared to fluorescence data, a different strategy was chosen for training DL for cell detection from bright-field images [40,49,56]. As the training data volume was substantially larger, a data generator was used for cropping the images to the correct size (288 × 288 pixels) instead of predefined training and validation sets.…”
Section: Methodsmentioning
confidence: 99%
“…The focal plane had been manually chosen in a prior step. As it has been previously shown that similar DL network architectures require considerably more bright-field data to converge to an optimal solution compared to fluorescence data, a different strategy was chosen for training DL for cell detection from bright-field images [40,49,56]. As the training data volume was substantially larger, a data generator was used for cropping the images to the correct size (288 × 288 pixels) instead of predefined training and validation sets.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, the datasets cover nine different cell lines, fixed and live cells, two different plate formats and two microscopes. The datasets provenances have been described previously 3 , 4 , 29 , 30 and we briefly describe their most important properties here.…”
Section: Methodsmentioning
confidence: 99%
“…However, the automated analysis techniques required to extract information at scale are often hindered by the artifacts present in the images 5 , 6 . Detecting and neutralizing the impact of such problematic image areas would provide more accurate results from experiments 3 , making artifact segmentation an important, albeit overlooked, research area in cell biology and beyond 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…A U-Net ( Ronneberger et al, 2015 ) is a CNN-based structure comprising an encoder, a decoder, and skip connections in between for segmentation. The architectural improvements of a U-Net-based structure yield even greater segmentation accuracy on microscopy images of cells or nuclei ( Ali et al, 2021 ; Caicedo et al, 2019 ; Raza, 2019 ). For instance, U-Net-based models such as StarDist ( Schmidt et al, 2018 ) and CellPose ( Stringer et al, 2021 ) have additional structures or outputs to segment images of crowded cells and nuclei effectively.…”
Section: Introductionmentioning
confidence: 99%